Potential Role of Glucose Transporter-1 Expression in Gastric Cancer: A Meta-Analysis and Systematic Review - Jianxin TAO; Ye ZHANG; Tong WANG (Tehran University of Medical Sciences, 2020)
Background: Glucose transporter-1 (GLUT-1) has been differentially expressed in various malignancies including gastric cancer (GC). Several previous meta-analyses of GLUT-1 have some significant limitations, such as researching the association between GLUT-1 and various cancer types with no specificity, not studying clinicopathological parameters with GLUT-1, existing conspicuous heterogeneity and so forth. Therefore, we performed a meta-analysis to evaluate the association between GLUT-1 expression and survival of gastric cancer patients, as well as clinicopathological characteristics. Methods: We systematically searched PubMed, Embase, Web of Science and China National Knowledge Infrastructure for relevant studies in accordance with the applicable criteria up to Aug 2017. Hazard ratios (HRs) and odds ratios (ORs) with their 95% confidence intervals (CIs) were used as the effective measures. Results: A total of 13 studies involving 1972 patients were included in this meta-analysis. The results demonstrated that there was a significant association between GLUT-1 expression and overall survival (OS) (HR=1.45, 95% CI=1.13-1.87) or disease-free survival (DFS) (HR=2.18, 95% CI=1.46-3.25). Moreover, GLUT-1 expression was significantly correlated with worse tumor nodes metastases (TNM) stage (OR=0.34, 95% CI=0.28-0.43), presence of lymph node metastasis (OR=2.88, 95% CI=1.34-6.19), intestinal type of Lauren classification (OR=3.84, 95% CI=2.57-5.74) and invasion of serosa (OR=0.25, 95% CI=0.18-0.35). Conclusion: Our meta-analysis showed that GLUT-1 was significantly correlated with poor OS and DFS in gastric cancer. Additionally, GLUT-1 was also a potential prognostic indicator of aggressive clinicopathological parameters in gastric cancer.